COUNSELING OF THE PILLARS OF DEMOCRACY IN INDONESIA IN THE FRAMEWORK OF THE PROJECT TO STRENGTHEN THE PROFILE OF PANCASILA STUDENTS (P5) PHASE F AT SMAN 1 KADIPATEN - Enang Rusnandi; Rosena Shintabella; Fikri Emsa Silmi; Fadli Emsa Zamani (Politeknik Mardira Indonesia, 2025)
The pillars of democracy are an important foundation in the life of the nation and state that must be understood by the younger generation, especially high school students. This service activity was carried out in the form of counseling on the pillars of Indonesian democracy to students of SMAN 1 Kadipaten, as part of the implementation of the Pancasila Student Profile Strengthening Project (P5) in Phase F. The main purpose of this activity is to foster students' critical awareness of the importance of democratic values in daily life and instill an active attitude as a responsible citizen. The methods used in this activity include material presentations, group discussions, and participant reflections. The results of the activity showed an increase in students' understanding of democratic principles, as well as the emergence of student initiatives in conveying aspirations and opinions in an orderly manner. This activity is a concrete step in instilling contextual and applicable national values in the educational environment.